Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To determine the result of the function [tex]\( \text{fun1}(x, y) \)[/tex] given [tex]\( x = 5 \)[/tex] and [tex]\( y = 2 \)[/tex], let's work through the function step by step:
1. Initial Call: The function is initially called with [tex]\( x = 5 \)[/tex] and [tex]\( y = 2 \)[/tex].
2. First Iteration: Check if [tex]\( x == 0 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 5) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(5 - 1, 5 + 2) = \text{fun1}(4, 7) \][/tex]
3. Second Iteration: Now, the function is called with [tex]\( x = 4 \)[/tex] and [tex]\( y = 7 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 4) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(4 - 1, 4 + 7) = \text{fun1}(3, 11) \][/tex]
4. Third Iteration: Now, the function is called with [tex]\( x = 3 \)[/tex] and [tex]\( y = 11 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 3) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(3 - 1, 3 + 11) = \text{fun1}(2, 14) \][/tex]
5. Fourth Iteration: Now, the function is called with [tex]\( x = 2 \)[/tex] and [tex]\( y = 14 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 2) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(2 - 1, 2 + 14) = \text{fun1}(1, 16) \][/tex]
6. Fifth Iteration: Now, the function is called with [tex]\( x = 1 \)[/tex] and [tex]\( y = 16 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 1) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(1 - 1, 1 + 16) = \text{fun1}(0, 17) \][/tex]
7. Final Iteration: Now, the function is called with [tex]\( x = 0 \)[/tex] and [tex]\( y = 17 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (True because } x = 0) \][/tex]
Since [tex]\( x == 0 \)[/tex], the function returns [tex]\( y \)[/tex]:
[tex]\[ \text{return } y = 17 \][/tex]
Thus, the function [tex]\( \text{fun1}(5, 2) \)[/tex] returns [tex]\(\boxed{17}\)[/tex].
1. Initial Call: The function is initially called with [tex]\( x = 5 \)[/tex] and [tex]\( y = 2 \)[/tex].
2. First Iteration: Check if [tex]\( x == 0 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 5) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(5 - 1, 5 + 2) = \text{fun1}(4, 7) \][/tex]
3. Second Iteration: Now, the function is called with [tex]\( x = 4 \)[/tex] and [tex]\( y = 7 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 4) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(4 - 1, 4 + 7) = \text{fun1}(3, 11) \][/tex]
4. Third Iteration: Now, the function is called with [tex]\( x = 3 \)[/tex] and [tex]\( y = 11 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 3) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(3 - 1, 3 + 11) = \text{fun1}(2, 14) \][/tex]
5. Fourth Iteration: Now, the function is called with [tex]\( x = 2 \)[/tex] and [tex]\( y = 14 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 2) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(2 - 1, 2 + 14) = \text{fun1}(1, 16) \][/tex]
6. Fifth Iteration: Now, the function is called with [tex]\( x = 1 \)[/tex] and [tex]\( y = 16 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 1) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(1 - 1, 1 + 16) = \text{fun1}(0, 17) \][/tex]
7. Final Iteration: Now, the function is called with [tex]\( x = 0 \)[/tex] and [tex]\( y = 17 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (True because } x = 0) \][/tex]
Since [tex]\( x == 0 \)[/tex], the function returns [tex]\( y \)[/tex]:
[tex]\[ \text{return } y = 17 \][/tex]
Thus, the function [tex]\( \text{fun1}(5, 2) \)[/tex] returns [tex]\(\boxed{17}\)[/tex].
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.